التدخل اللغوى - Rahmawati Rahmawati (AT-TA'LIM, 2012)
Developments and changes in a language occur because of changes in social, economic and cultural. The interchange between a language to another language is unavoidable. Interchange between language must have happened, for example, in vocabulary. Interference is a language error caused by the tendency of bias pronunciation (speech) of a language to another language. This paper describes about interference between Indonesian to Arabic in several aspects of language such as sounds (phonology), grammar forms of words (morphology), syntax (syntax), vocabulary (lexicon), grammar meaning (semantics), and culture .